Having a Mary heart in a Martha world : finding intimacy with God in the busyness of life - Weaver, Joanna (Colorado Springs, Colo. : WaterBrook Press, 2000)
With her fresh approach to the familiar Bible story, Joanna Weaver shows how all of us - Marys and Marthas alike - can draw closer to our Lord: deepening our devotion, strengthening our service, and doing both with less stress and greater joy.
A tale of two sisters -- Lord, don't you care? -- The diagnosis -- The cure -- Living room intimacy -- Kitchen service -- The better part -- Lessons from Lazarus -- Martha's teachable heart -- Mary's extravagant love -- Balancing work and worship -- Having a Mary heart in a Martha world -- Resources. Study guide -- Resources for living room intimacy -- Resources for kitchen service -- Journal the journey -- A simple plan for a half-day of prayer -- Christian rights in the workplace.
Includes bibliographical references.
Keywords: Christian women -- Religious life; Christian women -- Religious life